Trend of Nocturnal Enuresis in Children with Attention Deficit/Hyperactivity Disorder: A Nationwide Population-Based Study in Taiwan. (February 2017) - Tsai, Jeng-Dau; Wang, I-Chung; Chen, Hsuan-Ju; Sheu, Ji-Nan; Li, Tsai-Chung; Tsai, Henry J; Wei, Chang-Ching
Attention-deficit/hyperactivity disorder (ADHD) and nocturnal enuresis are common disorders with extensive psychosocial suffering in affected children, and healthcare burden on parents. Whether the childhood psychological disorders and nocturnal enuresis are factors contributing to ADHD have not been clearly established. This study conducted a population-based case–control study using data sets from the National Health Research Insurance database, and identified 14 900 children diagnosed with ADHD. Risk factors that have been associated with or possibly related to ADHD development were included in this study. Performance of in groups of ADHD with enuresis was compared with controls. With adjustment for potential covariates, participants with enuresis exhibited a 2.24-fold greater risk of subsequent ADHD development compared with controls (95% CI 1.84 to 2.73). Participants with enuresis and comorbidity had a significantly greater risk of ADHD than those with no enuresis and no comorbidity (adjusted OR=8.43, 95% CI 4.38 to 16.2). Children who are assessed for ADHD should be evaluated for the presence of enuresis or other neurobehavioral comorbidities. Multidisciplinary treatment may benefit children with ADHD and minimize psychological burden on parents.